Analysis of river restoration and stabilization practitioners, their design tools and limits - Miller, Eli Scott (Kansas State University, 2022)
One of the many consequences of anthropogenic influence on streams is accelerated stream erosion. The industry of stream restoration and/or stabilization has grown to meet the needs of this consequence. Despite its magnitude there are many issues regarding the vagueness of objectives and guidelines that have impacted the success of stream restoration and/or stabilization projections. The objectives of this study were to create a detailed understanding of the tools and design guidelines practitioners use in the field, describe the constraints that affect practitioners’ ability to perform in the field and develop a HEC-RAS model that reflects its use in the practice through application to a planned bank stabilization project in Kansas. A survey was created to examine aspects of the design process (guidelines, data, and models) employed by stream practitioners as well as determine the relative influence of factors such as funding, time, location, on their ability to design projects. In addition, a HEC-RAS model was created for a case study streambank stabilization project on the Cottonwood River in east-central Kansas to determine its ability as a design tool to assist in predicting hydraulic conditions and erosion for a future stream restoration projects. The practitioner survey provides a benchmark for current practices and constraints for practitioners in the stream restoration/stabilization industry, with the primary results being: (1) HEC-RAS is the predominant computational model used by practitioners, (2) many other potential models are not utilized due to lack of training and time, (3) respondents who did not use models did so due to their ineffectiveness and difficulty of use, (4) guidelines used were highly varied but were mostly based off of Rosgen’s Natural Channel Design methods (with few exceptions by region), (5) practitioners within governmental organization use guidelines primarily due to regulations and not their effectiveness, (6) the waiting time on permits can be damaging to the success of the project, and (7) more long term data is needed to support project design, including suspended sediment, sediment bedload and subsurface flow. The results from the HEC-RAS model demonstrated that while possible locations for erosion can be found using the model, erosion rates are unreliable to determine using just shear stress as an indicator. This study recommends the following items. The first is to educate practitioners to use models like HEC-RAS and to use that education system in part to collect long term data that would improve the field. The second is to continue studying the Cottonwood River and implementation of streambank stabilization structures over time using HEC-RAS to determine its long-term accuracy.
Keywords: Stream restoration; Streambank stabilization; HEC-RAS; Streambank erosion; River training; Bioengineering